Engineering Digital Transformation Proceedings of the 11th International Conference on Industrial Engineering and Industrial Management - Ortiz, Ángel; Andrés Romano, Carlos; Poler, Raul; García-Sabater, José-Pedro (Lecture Notes in Management and Industrial Engineering, 2019)
This book outlining the latest developments in engineering digital transformation gathers a selection of the best papers presented at the 11th International Conference on Industrial Engineering and Industrial Management (CIO 2017), held in Valencia, Spain, from July 5th to 6th, 2017. The papers discuss topics in the following areas: strategy and entrepreneurship, OR, modelling and simulation, production, logistics and supply chain management, information systems, quality and product management, knowledge and project management, service systems, and education.